2019
DOI: 10.21203/rs.2.19723/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reactive Case Detection of Asymptomatic Malaria in Households and Neighbors of Laboratory Confirmed Cases in Raya Kobo District, Northeast Ethiopia

Abstract: Background Malaria is the leading vector borne parasitic disease causing enormously high morbidity and mortality worldwide. There have been huge efforts so far to control and eliminate malaria in the world. However, high prevalence of asymptomatic carriage poses a threat on malaria control and elimination programs. Since asymptomatic infections present no overt sign and symptoms, they do not get clinical attention. Moreover, asymptomatic cases are a potential source of infection in high and low transmission se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 24 publications
0
11
1
Order By: Relevance
“… 25 The age group used for analysis was not consistent across the studies. Of the 14 studies included in the final analysis, 7 were conducted in Amhara Region, 26 32 4 in SNNPR, 24 , 33 35 2 in Oromia, 25 , 36 and 1 in Benishangul-Gumuz. 37 Fifty percent of the studies were community-based.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… 25 The age group used for analysis was not consistent across the studies. Of the 14 studies included in the final analysis, 7 were conducted in Amhara Region, 26 32 4 in SNNPR, 24 , 33 35 2 in Oromia, 25 , 36 and 1 in Benishangul-Gumuz. 37 Fifty percent of the studies were community-based.…”
Section: Resultsmentioning
confidence: 99%
“… 37 Fifty percent of the studies were community-based. 27 29 , 32 , 33 , 35 , 36 The outcome measure was only RDT for two studies, 27 , 37 only microscope for five studies, 24 , 28 , 29 , 31 , 35 and both microscopy and RDT for seven studies. 25 , 26 , 30 , 32 34 , 36 The studies done by microscopy have identified the species, while two of the RDT result did not ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations